Colors of change - Calaway, J. Albert; O'Hamlin, S. Birkaen (Springfield, Mo. : Jabs Publishing, 1989)
A novel about a family's struggle through the world of drugs and a long prison sentence that demands that a man and his son learn to change.
Keywords: Drug abuse -- Juvenile fiction